PTU-107 Defining the low-risk inactive carrier in chronic hepatitis b with qhbsag: do the same rules apply in children and young adults?. (22nd June 2015) - Hansi, N; Gill, US; Banerjee, M; Naik, S; Tong, W; Foster, GR; Carey, I; Kennedy, PT
Abstract : Introduction: A substantial proportion of e-Antigen negative chronic hepatitis B (CHB) under specialist follow-up are inactive carriers (IC) defined as those with low serum ALT and HBV DNA. Recent studies have described the potential utility of quantitative Hepatitis B surface antigen (qHBsAg) (<1, 000 IU/ml) to represent a low-risk IC state, which is associated with reduced risk for disease progression and the development of HCC. Conversely higher qHBsAg levels (>1, 000 IU/ml) are associated with an increase in risk of disease progression. 1 Accurate identification of low-risk IC's would reduce the frequency of follow-up and the need for HCC screening in selected patients. We investigated whether a qHBsAg threshold (<1, 000 IU/ml) representing a low-risk IC profile can be applied to children and young adults with CHB. Method: Fifty-six consecutive treatment naïve eAg negative young patients (<30 years) considered IC's (ALT <40, HBV DNA <2, 000 IU/ml) over longitudinal follow-up were analysed; female = 38, median age = 26 years (range 12–30 years). A cohort of older patients (>30 years) based on the same parameters were included for comparison; female = 33%, median age = 42 years (range 31–61 years). HBsAg levels were quantified in all patients to determine any correlation between the qHBsAg threshold (<1, 000 IU/ml) and age. Results: In keeping with an IC disease profile, serum ALT and HBV DNA levels in both cohorts were similar (p = ns), however, qHBsAg levels were significantly higher in the <30s vs. >30s; mean qHBsAg 10, 545 IU/ml vs. 5, 278 IU/ml (p = 0.006). In accordance with this we detected a significant negative correlation with age and qHBsAg (Spearman Rho rs = -0.35, p = 0.0004). A significantly higher proportion of older patients had qHBsAg <1, 000 IU/ml, (36% vs. 13%, p = <0.001), consistent with low-risk IC state. Conclusion: The addition of qHBsAg to serum ALT and HBV DNA can enhance risk stratification. However, a threshold level (<1, 000 IU/ml) cannot be safely utilised in young patients to define a low-risk IC state. The natural decline in qHBsAg with advancing age underlines the need for further studies to define an age limit above which this qHBsAg level (<1, 000 IU/ml) can be used to identify low-risk ICs and streamline clinical monitoring. Disclosure of interest: None Declared. Reference: Tseng TC, Liu CJ, Yang HC, et al . High levels of hepatitis B surface antigen increase risk of hepatocellular carcinoma in patients with low HBV load. Gastroenterology 2012;142:1140–1149